Dificultades para la atención en los servicios de urgencias: la espera inhumana (2010)
ABSTRACT: To understand the process of receiving emergency care services for patients and their families. Methodology: the research was performed with adult people from both genders who consulted the emergency room services in the city of Medellin (Colombia). A qualitative focus was used with focalized ethnographic tools, 9 interviews and 50 observation hours were conducted. The analysis was done from the field journals and interviews, codes were extracted and then grouped in categories that best represented the studied phenomenon. Results: people assist to the emergency service looking for care, but when they get there they find themselves with a series of barriers that should be handled to be able to be admitted, to receive information and to be accompanied. In the emergency service there is a disagreement between three views: the first one is the one from the participants who consider it inhuman, the second one is the health system one that ensures timely and quality care, and the third one is the one shown in other researches: they have found access barriers for admission and information. Conclusion: there are a number of barriers for patients to receive care in the emergency room services in the studied institutions.